EXPERIMENTAL STUDY OF COOLING SPRAY METHOD ONTO INCLINED HEATED SURFACES - Wibowo, Teguh; Hermawan, Dedet; Prakoso, Agung (Vortex, 2022)
Single droplet impingement onto inclined heated surface is studied experimentally. Droplet in the form of aquades is dropped from a fixed height 70 mm to the metal surface with 45º impact angle. This experiment uses 3 types of metals; Stainless Steel AISI 304, Aluminum Alloy 2024, and Copper. All material surfaces are mirror polished and assumed to have the same surface treatment condition. Surface temperatures are 110 ºC, 150 ºC and 210 ºC to determine droplet behavior characteristics. The droplet has 3.0 mm diameter and 28.5 Weber Number (low impact category). In order to analyze droplet behavior in slow motion high velocity camera 4000 fps (frames per second) is used with image resolution 1024 x 768. Data obtained then processed using MATLAB image processing technique to analyze sequence of images visually and quantitatively to determine several parameters; spreading ratio, dimensionless height and contact time.The results showed droplets have different behavior characteristics even at the same surface temperature. Droplet contact time on the copper surface is shorter than aluminum and stainless steel. This is because droplets experienced bouncing due to film boiling regime takes place earlier. Maximum spreading ratio of stainless-steel surfaces is higher than copper because changes of boiling regime on stainless steel surfaces are slower and droplet is still experiencing spreading on the surface